TO WHAT EXTENT THE DECLARATION OF A STATE OF EMERGENCY IS CONSISTENT WITH THE PALESTINIAN BASIC LAW DURING THE COVID-19 PANDEMIC (UUM Journal of Legal Studies, 2024)
The COVID-19 pandemic has raised consciousness across the globe of how constitutions respond to crises. This article examines the issue of the Palestinian President declaring a state of emergency in Palestine on March 5, 2020, under Presidential Decree No. 1 of 2020, to confront the spread of the Coronavirus. However, the President continues to extend the thirty-day state of emergency ten times. In addition, the article discusses a crucial issue associated with the extent to which the extended constitution of emergency in Palestine lasts, as the Basic Law only allows him to declare the state of emergency for a one-time limit. The article aims to clarify the constitutionality of the extension of the state of emergency in Palestine, in addition to placing some legal alternatives to avoid the President’s breach of the Basic Law. To achieve the objectives of the article, socio-legal research using a qualitative approach and face-to-face interviews was adopted. Accordingly, findings show the inconsistency of the extension of the state of emergency with the Basic Law due to the suspension of the role of the Legislative Council in Palestine. The article emphasizes and recommends that the role of the Legislative Council shall be activated to oversee the presidential decrees extending a state of emergency issued by holding the legislative elections in Palestine.